Indonesia’s public vulnerability to ethnic and religious information - Nikolaus Prathama; Lenny Bernadeta; Gita Juniarti; Yowan Tamu; Retno Irianto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This study aims to determine the extent to which ethnic and religious information is believed to be fake news or facts and is spread to people close to them. This type of research is qualitative using a phenomenological approach, namely collecting experience data and testing individual assessments through an experimental stage from a sample of 30 non-expert millennials and gen z in the city of Semarang, Indonesia. The findings of this study reveal several attitudes formed by participants. First, participants believe that fake news still exists and is spread predominantly online. Second, participants believe that they will not be trapped by fake news and have credibility. Third, respondents discuss suspicious information with reference groups. Fourth, dissonance is still prominent in the assessment of information status (fake or fact) and the culture of collectivism appears prominent in this study.